Development and validation of an optimized HPLC-UV analytical method for the quantification of 5-methyltetrahydrofolate (Active Folate) in dietary supplements: Application to commercial tablets and capsules - Alshishani, Anas; Shalash, Marwan; Aldalaty, Aya; Shaghlil, Lena (Elsevier Inc., 2024)
5-MTHF is the active form of folic acid, and it is provided as a dietary supplement in the market. Therefore, in this study we provide a new, simple and economic HPLC-UV analysis method to quantify 5-MTHF in dietary supplement. A new HPLC-UV method was developed and validated for the quantification of 5-methyltetrahydrofolate in dietary supplements. The method was optimized in terms of chromatographic conditions, including the mobile phase composition, chromatographic column, and the sample preparation diluent using ascorbic acid. A combination of ammonium acetate buffer with methanol (90:10) was the optimal mobile phase, achieving a retention time of approximately 11.4 min on C18 column with good column performance (N = 6786, Asymmetry = 1.03). The method was validated for selectivity, linearity, precision, accuracy, and robustness. The calibration curve was linear (r2 > 0.999) over the concentration range of 1.20 to 4.80 µg/mL. Precision was demonstrated with RSD% values ranging from 1.38 % to 2.90 % for intra-day precision and 0.96 % to 2.61 % for inter-day precision. Accuracy was confirmed with recovery values between 96.5 % and 110.6 % for spiked samples. To demonstrate the method’s applicability, ten brands of 5-MTHF dietary supplements were collected from local pharmacies. Assay results showed significant variability, with four brands having contents below the acceptable range (90–110 % of labeled contents) and two brands exceeding this range. The stability of 5-MTHF in these products appeared to be formula-dependent, emphasizing the need for regulatory revisions to mandate stability testing for dietary supplements.